Organizational and leadership factors affecting the quality of nurse performance in hospitals - Twistiandayani, Retno; Prameswari, Rizki Dwi; Ayatulloh, Daviq; Priyantini, Diah (Intelektual Pustaka Media Utama, 2025)
The purpose of this study was to analyze organizational and leadership factors that affect the quality of nurse performance in hospitals. A cross-sectional study in 162 respondents conducted at Universitas Airlangga Hospital in May-June 2021. Variable organizational factors (resources, rewards, work structure, and design), leadership factors (competence, job meaning, autonomy, and impact), and the quality of nurse performance were measured using a questionnaire that had been modified by the researcher and declared valid (r table=0.351-1.000) and reliable (0.919-0.980), the data were then analyzed using logistic regression. Organizational factors consisting of resources (p=0.001), rewards (p=0.012), structure (p=0.029), and work design (p=0.013) showed a significant relationship with the quality of work, as well as organizational factors consisting of competence (p=0.043), job meaning (0.035), autonomy (0.021) and impact (0.025). The strongest results are shown in the quality of nurse resources. Improving the quality of performance of nurses must pay attention to organizational factors and influencing leadership factors, with the most dominant factor being the quality of nurse resources.